Justinian, Pilgrimages and the Theotokos: Imperial Propaganda in De Aedificiis V - Biamino, Martina (Studia Ceranea, 2023)
This article analyses Book V of De Aedificiis, specifically focusing on Aed. V, 6–9. Building on previous studies that demonstrate Procopius’ journey within this book along an ancient road traditionally used by pilgrims, it is noted how, in what can be considered the second part of the book, the historian focuses on the churches built by Justinian for the Theotokos, all situated on high points in Palestine. Based on this, the article seeks to explain how this insistence on the churches of the Virgin on hillsides, combined with the theme of pilgrimage, serves court propaganda, which may have promoted a de-Judaization and a de-Nestorianization of Palestine. Additionally, it is hypothesized that Procopius may have drawn inspiration, given the subject matter, from a genre closely related to pilgrimage, such as that of itineraria.